2022
DOI: 10.1002/admi.202201716
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Spin‐to‐Charge Interconversion in Weyl Semimetal TaP at Room Temperature

Abstract: In this paper, spin‐to‐charge current conversion properties in the Weyl semimetal TaP by means of the inverse Rashba–Edelstein effect (IREE) with the interfacial integration of this quantum material with the ferromagnetic metal Permalloy (Py = Ni81Fe19) are presented. The spin currents are generated in the Py layer by the spin pumping effect (SPE) from microwave‐driven ferromagnetic resonance and are detected by a dc voltage along the TaP crystal, at room temperature. A field‐symmetric voltage signal is observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…The direct and inverse Rashba–Edelstein effects have been explored in different systems such as graphene, transition metal dichalcogenides (TMDs), LaAlO 3 /SrTiO 3 , Bi/Ag and nGaAs/InGaAsP interfaces, and in topological insulators. Among materials with surface states, antimony (Sb) has proven to be a unique material. Sb is not only an elemental material but also a constituent element of several topological materials, and it can be a topological insulator by itself. , Furthermore, a recent study showed that Sb films can be grown by sputtering without the need of heat treatment or the use of special substrates and still present surface states .…”
Section: Introductionmentioning
confidence: 99%
“…The direct and inverse Rashba–Edelstein effects have been explored in different systems such as graphene, transition metal dichalcogenides (TMDs), LaAlO 3 /SrTiO 3 , Bi/Ag and nGaAs/InGaAsP interfaces, and in topological insulators. Among materials with surface states, antimony (Sb) has proven to be a unique material. Sb is not only an elemental material but also a constituent element of several topological materials, and it can be a topological insulator by itself. , Furthermore, a recent study showed that Sb films can be grown by sputtering without the need of heat treatment or the use of special substrates and still present surface states .…”
Section: Introductionmentioning
confidence: 99%